(untitled) - Raote, Komilla (New Delhi, 1998)
Her husband is a great figure in local lore, but the King is not remembered today on a personal level. He was said to be a great man, strong and fair, and a great warrior. He is depicted in ancient paintings to be a gentle man with his wife, but a force to be reckoned with on the battlefield. His face in these paintings varies from warm and handsome to dark and devilish, but always it is very apparent by his physique that he was a very powerful man: large, muscled (for he always appeared with torso exposed in those paintings depicting war scenes) chest, an abdomen that told the story of seemingly ten-thousand crunches daily, and a slim waist, large, strong thighs and calves, and always topped by thick, wild, dark brown hair streaked with red. It is not hard to imagine him being mistaken by the King of the Gods himself, Zeus, on the battlefield.
Keywords: Folk literature,Văn học dành cho trẻ em,Văn học dân gian; India,Ấn Độ